Investigation of Reliability on Structural Analysis on Oil Pan Bolt Feeder Machine: A Short Review - Hazim, Rafiq; Ariffin, Ahmad Hamdan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The aim of this work is to investigate the reliability of the structural model of oil pan bolt feeder machine in the industry. Generally, oil pan bolt feeder machine is a custom-made machine by Double One Precision Engineering Sdn. Bhd. that is used to feed bolt and at the same time it can fasten to a component automatically. The work will apply finite element method (FEM) by using SolidWorks2018. The model will be drawn according to its Computer aided-design (CAD) data then apply some load to the model to get the factor of safety of the model. Next, repeat the same procedure by applying different types of aluminium alloy to get the best kind of aluminium frame for the model. The result from the test indicates the reliability and level of user friendly of the model. It helps the industry in increasing the quality of their products which also guaranteed the lesser expense. The results obtained also indicates the tensile strength, the weight and the price of the aluminIum alloys on today’s market.